Effects of intravitreal bevacizumab on reduced visual acuity and macular thickness secondary to branch retinal vein occlusion - Eltutar K (Dove Medical Press, 2013)
Kadir Eltutar, Fahreddin Acar, Nurhan Dincer, Sibel Zirtiloglu, Erkan Unsal Istanbul Training and Research Hospital, Istanbul, Turkey Background: The purpose of this study was to evaluate the effects of intravitreal bevacizumab injection in the treatment of macular thickness and reduced visual acuity in patients with branch retinal vein occlusion. Methods: In this retrospective study, we evaluated 15 eyes of 15 consecutive patients diagnosed with branch retinal vein occlusion between May 2008 and June 2011 at our institution. Detailed ophthalmologic examination, optical coherence tomography, and/or fundus fluorescein angiography was performed at diagnosis and during follow-up. A 1.25 mg intravitreal bevacizumab injection was administered to all patients on average 2.73 (1–7) times. Visual acuity and macular thickness were evaluated before and after treatment. Results: Eleven patients were female (73.3%) and four were male (26.6%). The mean patient age was 62.6 years. The patients were followed for a mean of 11.4 (range 4–24) months. Mean best-corrected visual acuity was 0.92 ± 0.52 logMAR (logarithm of the minimum angle of resolution) before treatment and 0.66 ± 0.42 logMAR at the last examination. The increase in visual acuity was found to be statistically significant (P = 0.031). Mean macular thickness was 395.46 ± 106.55 µm before treatment and 302.26 ± 84.6 µm after the final treatment. The decrease in macular thickness was statistically significant (P < 0.001). Conclusion: Intravitreal bevacizumab injection was effective for treatment of retinal vein branch occlusion. Keywords: branch retinal vein occlusion, bevacizumab, macular thickness, optical coherence tomography